Extending Health Insurance to the Rural Population : An Impact Evaluation of China's New Cooperative Medical Scheme - Wagstaff, Adam (2012)
In 2003, China launched a heavily subsidized voluntary health insurance program for rural residents. We combine differences-in-differences with matching methods to obtain impact estimates, using data collected from program administrators, health facilities and households. The scheme has increased outpatient and inpatient utilization, and has reduced the cost of deliveries. But it has not reduced out-of-pocket expenses per outpatient visit or inpatient spell. Out-of-pocket payments overall have not been reduced. We find heterogeneity across income groups and implementing counties. The program has increased ownership of expensive equipment among central township health centers but has had no impact on cost per case.